High-heat-insulation phase change paraffin-SiO2 aerogel composite fiber material and preparation method thereof

By introducing phase-change paraffin into SiO2 aerogel and using cationic surfactants and high-temperature glass fiber substrates, the poor thermal insulation performance of silica aerogel materials and the difficulty of dispersing phase-change materials in fiber materials are solved. Phase-transformed paraffin-SiO2 aerogel composite fiber material that achieves efficient thermal insulation and mechanical performance improvement.

CN119191814APending Publication Date: 2024-12-27IBIH ADVANCED MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411335273.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing silica aerogel materials have poor thermal insulation performance at high temperatures, and phase change materials are difficult to disperse and fix evenly in fiber materials, resulting in uneven thermal insulation and insufficient mechanical strength.

Method used

Phase-change paraffin is introduced into SiO2 aerogel, and the cationic surfactant and high-temperature treated glass fiber substrate are used to achieve uniform dispersion and fixation of phase-change paraffin through composite sol and vacuum impregnation technology, thereby improving thermal insulation and mechanical properties.

Benefits of technology

It significantly improves the thermal insulation performance and mechanical toughness of phase-changed paraffin-SiO2 aerogel composite fiber material, solves the dispersion and fixation problems of phase-changed materials in fiber materials, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191814A_ABST
    Figure CN119191814A_ABST
Patent Text Reader

Abstract

The invention discloses a phase-change paraffin-SiO2 aerogel composite fiber material, which is prepared by compounding molten phase-change paraffin and SiO2 sol, dispersing the phase-change paraffin and SiO2 sol by using a surfactant and assisting in constructing a SiO2 gel frame, and preparing the phase-change paraffin-SiO2 aerogel composite fiber material by using a glass fiber base material treated at high temperature as a support material. The phase change paraffin-SiO2 aerogel composite fiber material is prepared and obtained; the phase-change paraffin, the SiO2 aerogel and the glass fiber base material are compounded through simple, convenient and controllable operation, the problems that the phase-change paraffin is difficult to disperse, control, leach and immerse during compounding are solved, the obtained phase-change paraffin-SiO2 aerogel composite fiber material has super-high heat insulation and heat storage performance and good toughness, and meanwhile, the phase-change paraffin, the SiO2 aerogel and the glass fiber base material can be used for preparing the composite fiber material. The preparation method is convenient and stable, and has wide application value and potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a highly thermally insulating phase-change paraffin wax-SiO2 aerogel composite fiber material and a preparation method thereof. Technical Background

[0002] Aerogel is a lightweight nano-solid material with a nano-scale porous network structure and a large amount of gaseous dispersion medium in the network skeleton. Due to its unique structure, aerogel materials have been widely studied. Compared with other aerogels, silica aerogel has abundant raw material sources, simple process, good controllability, high porosity, high temperature resistance, low thermal conductivity and high specific surface area. Therefore, it has been widely studied. However, silica aerogel also has some problems. Due to the long wavelength of infrared radiation, silica aerogel with nano-scale pore structure cannot effectively block radiation heat transfer, resulting in high radiation transmittance, high high-temperature thermal conductivity and poor high-temperature thermal insulation performance; at the same time, aerogel insulation can only delay the propagation of thermal runaway, but cannot completely prevent the propagation of thermal runaway. Finally, silica aerogel usually has poor mechanical strength and is fragile, making it difficult to apply to the field of thermal insulation.

[0003] Phase change material PCM refers to a material that can achieve reversible transformation between two material states at a certain constant temperature (i.e. phase change temperature) and can absorb or release a large amount of heat during the transformation process. It is a high-quality latent heat storage material. Phase change materials include inorganic phase change materials (salt hydrates, metals), organic phase change materials (normal alkanes, normal alkanols, normal alkanoic acids, normal alkanoic acid esters, polyethers, comb polymers, polyurethanes, etc.) and composite phase change materials (inorganic-inorganic, organic-organic, inorganic-organic). Different types of phase change materials have different enthalpy values ​​and phase change temperatures. Due to their unique heat storage and release characteristics, phase change materials were first used in astronaut clothing and to protect precision instruments for space experiments. However, all phase change materials have two problems. One is that they are prone to leakage and pollution during the phase change process, especially when changing from solid to liquid; the other is that the viscosity increases significantly during the phase change process, making it difficult to disperse evenly. This makes the further application of phase change materials very difficult, especially when it is introduced into fiber materials. Not only can the phase change material not be evenly distributed, resulting in uneven thermal insulation, but the unique pore structure of the fiber itself also further hinders the infiltration of phase change wax. Even if the infiltration of the phase change material is achieved, there is still a lack of interaction between the phase change material and the fiber material, or the fiber structure is destroyed or the phase change wax is leached out due to the inability to accurately control the amount of phase change material infiltration. It is very difficult to construct a phase change material SiO2 aerogel composite fiber material with precise controllable, uniform dispersion, stable structure, and excellent thermal insulation performance. Summary of the invention

[0004] The present invention aims at the problems in the prior art. The thermal insulation performance of the phase change paraffin-SiO2 aerogel composite fiber material is improved by introducing phase change paraffin into SiO2 aerogel; the melted phase change paraffin is mixed with SiO2 sol to accurately control the amount of phase change paraffin added; a surfactant is used to evenly disperse the composite sol and assist in constructing the SiO2 gel framework, thereby achieving even dispersion of the phase change paraffin; a high-temperature treated glass fiber substrate is used as a supporting material to further optimize the mechanical properties of the phase change paraffin-SiO2 aerogel composite fiber material, thereby solving the problem of lack of fixation of the phase change paraffin in the fiber material, and fully improving the thermal insulation capacity and various performances of the phase change paraffin-SiO2 aerogel composite fiber material.

[0005] The preparation method of the phase change paraffin wax-SiO2 aerogel composite fiber material proposed by the present invention is as follows Figure 1 , specifically including the following steps:

[0006] S1: Preparation of SiO2 sol: Mix the silicon source and alcohol evenly according to the molar ratio of silicon source: alcohol = 1: (4-20), and add an appropriate amount of acidic catalyst for hydrolysis;

[0007] S2: Compounding of phase change wax and SiO2 sol: adding melted phase change wax into SiO2 sol and stirring, adding alkaline catalyst and cationic surfactant at the same time, and mixing into a uniform composite sol, wherein the mass of phase change wax in SiO2 sol accounts for 0.1%-10%;

[0008] S3: Treatment of glass fiber substrate and preparation of gel: The glass fiber substrate after high temperature treatment is placed in the composite sol for vacuum impregnation and gelation;

[0009] S4: Aging: After the S3 gel becomes hard, put it into the aging solution for aging;

[0010] S5: Drying: After aging, ethanol supercritical drying is used to obtain a phase change paraffin-SiO2 aerogel composite fiber material.

[0011] As some exemplary preferred schemes, the silicon source in step S1 is selected from any one of orthosilicates and silanes.

[0012] As a further solution, the alcohol in step S1 is selected from a mixture of one or more monohydric alcohols.

[0013] As a further solution, the ratio of silicon source:alcohol in step S1 is 1:(10-20).

[0014] As a further solution, the acidic catalyst in step S1 is selected from any one of a strong acid or a medium-strong acid.

[0015] As a further solution, the pH value during the hydrolysis in step S1 is 1.5 to 3.0.

[0016] As a further solution, the hydrolysis temperature in step S1 is 25°C-50°C.

[0017] As a further solution, the hydrolysis time in step S1 is 3-16 hours.

[0018] As a further solution, the phase change paraffin in step S2 is selected from 28-80 series phase change paraffin.

[0019] As a further solution, the phase change wax is selected from 28-40 series phase change wax.

[0020] As a further solution, the phase change paraffin wax in step S2 accounts for 0.5%-3% by mass in the SiO2 sol.

[0021] As a further solution, the alkaline catalyst in step S2 is selected from a mixed solution of an alkaline compound and deionized water.

[0022] As a further solution, the mass ratio of the alkaline catalyst to the deionized water in step S2 is alkaline compound:deionized water=1:100.

[0023] As a further solution, the mass ratio of the alkaline catalyst to the composite sol in step S2 is 1:100-1:20 (adjusted according to the required gel time).

[0024] As a further solution, the cationic surfactant in step S2 is selected from any one of an amine salt type cationic surfactant, a quaternary ammonium salt type cationic surfactant and a heterocyclic type cationic surfactant.

[0025] As a further solution, the cationic surfactant in step S2 is selected from any one of a quaternary ammonium salt cationic surfactant and a heterocyclic cationic surfactant.

[0026] As a further solution, the cationic surfactant in step S2 is selected from quaternary ammonium salt cationic surfactants.

[0027] As yet a further embodiment, the quaternary ammonium salt type cationic surfactant is selected from quaternary ammonium salt type cationic surfactants having a C10-C20 long-chain alkyl group.

[0028] As a further solution, in step S2, the mass of the surfactant in the SiO2 sol accounts for 0.1%-10%.

[0029] As a further solution, the high temperature treatment method in step S3 is not limited, and technicians can choose according to actual needs, including muffle furnace calcination, tubular furnace calcination, and electric arc furnace calcination.

[0030] As a further solution, the glass fiber substrate treatment temperature in step S3 is 250°C-400°C.

[0031] As a further solution, the glass fiber substrate treatment temperature in step S3 is 280°C-350°C.

[0032] As a further solution, the glass fiber substrate treatment time in step S3 is 3h-6h.

[0033] As a further solution, the glass fiber substrate treatment time in step S3 is 3.5h-4.5h.

[0034] As a further solution, the vacuum degree of the vacuum box in step S3 is -0.15MPa to -0.05MPa.

[0035] As a further solution, the immersion time in step S3 is 5-15 minutes.

[0036] As a further solution, the gel time in step S3 is 50-180 min.

[0037] As a further solution, the aging liquid in step S4 is selected from alcohols, silanes or a mixture of both.

[0038] As a further embodiment, the alcohol is selected from one or a mixture of two monohydric alcohols.

[0039] As a further embodiment, the silanes are selected from one or a mixture of organic silanes, inorganic silanes, and fluorinated silanes.

[0040] As a further solution, the aging temperature in step S4 is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, or 70°C.

[0041] As a further solution, the supercritical temperature of ethanol in step S5 is 250-270°C.

[0042] As a further solution, the supercritical pressure of ethanol in step S5 is 8-12 MPa.

[0043] Compared with the prior art, the present invention has at least the following beneficial effects:

[0044] The present invention introduces phase change paraffin into SiO2 aerogel, uses cationic surfactant as template and dispersant, combines high temperature treatment of glass fiber substrate, optimizes material ratio, solves the difficult problems of difficult dispersion, difficult immersion, difficult control, and easy leaching faced by phase change paraffin compounding, and successfully prepares phase change paraffin-SiO2 aerogel composite fiber material with synergistically improved thermal insulation performance, heat storage performance, and material toughness. At the same time, the preparation method has convenience and stability, which is conducive to industrial production, and therefore has broader application potential and value. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0046] Figure 1 This is a flow chart for the preparation of phase change paraffin-SiO2 aerogel composite fiber materials.

[0047] Figure 2 This is a comparison chart of the thermal insulation performance of 28 paraffin waxes dried with different proportions of ethanol supercritical and CO2 supercritical drying.

[0048] Figure 3 This is the SEM morphology of the SiO2 aerogel composite wet-process glass fiber felt material prepared in Comparative Example 1.

[0049] Figure 4 This is the SEM morphology of the 1% 28 paraffin-SiO2 aerogel composite wet-process glass fiber felt material prepared in Example 2.

[0050] Figure 5 This is the SEM morphology of the CO2 supercritical dried 1% 28 paraffin-SiO2 aerogel composite wet-process glass fiber felt material prepared in Comparative Example 8.

[0051] Figure 6 This is the structural diagram of the thermal insulation test platform.

[0052] For ease of understanding, the phase-change paraffin wax-SiO2 aerogel composite fiber material of the present invention will be described more comprehensively below, and examples of the present invention will be given, but the scope of the present invention is not limited thereby.

[0053] In order to solve the problems of difficult dispersion, easy leaching and easy destruction of fiber material structure faced when phase change paraffin is introduced into fiber material, and to improve the thermal insulation performance of SiO2 aerogel composite fiber material, the present invention proposes a phase change paraffin-SiO2 aerogel composite fiber material, which significantly improves the thermal insulation performance of SiO2 aerogel fiber material and increases the heat storage function by introducing phase change paraffin into SiO2 aerogel composite fiber material and utilizing the characteristic of absorbing or releasing a large amount of heat during the phase change process of phase change paraffin; by compounding phase change paraffin and SiO2 sol into composite sol, the viscosity of phase change paraffin is reduced and the addition amount is precisely controlled; by regulating the type of surfactant, highly uniform dispersion of phase change paraffin is achieved, and surfactant is used to assist the composite sol to form a structurally stable framework; by high-temperature calcination treatment of glass fiber substrate, the problem of lack of fixation of phase change paraffin is solved, leaching of phase change paraffin is avoided, and the thermal insulation performance and energy utilization rate of phase change paraffin-SiO2 aerogel composite fiber material are fully improved.

[0054] On the basis of the above, the present invention fully considers the effects of the type and dosage of phase change paraffin, the type of additives and the fiber substrate on the phase change paraffin-SiO2 aerogel composite fiber material, and ensures the good thermal insulation and heat storage performance of the phase change paraffin-SiO2 aerogel composite fiber material by adjusting the appropriate type and mass ratio in the material, and further improves the performance of the phase change paraffin-SiO2 aerogel composite fiber material by optimizing various parameters.

[0055] The preparation method of the phase change paraffin wax-SiO2 aerogel composite fiber material proposed by the present invention is as follows Figure 1 , specifically including the following steps:

[0056] S1: Preparation of SiO2 sol: Mix the silicon source and alcohol evenly according to the molar ratio of silicon source: alcohol = 1: (4-20), and add an appropriate amount of acidic catalyst for hydrolysis;

[0057] S2: Compounding of phase change wax and SiO2 sol: adding melted phase change wax into SiO2 sol and stirring, adding alkaline catalyst and cationic surfactant at the same time, and mixing into a uniform composite sol, wherein the mass of phase change wax in SiO2 sol accounts for 0.1%-10%;

[0058] S3: Treatment of glass fiber substrate and preparation of gel: The glass fiber substrate after high temperature treatment is placed in the composite sol for vacuum impregnation and gelation;

[0059] S4: Aging: After the S3 gel becomes hard, put it into the aging solution for aging;

[0060] S5: Drying: After aging, ethanol supercritical drying is used to obtain a phase change paraffin-SiO2 aerogel composite fiber material.

[0061] Phase change paraffin is a common organic phase change paraffin with the advantages of high heat storage, high thermal insulation, good stability and non-toxicity. The introduction of phase change paraffin into SiO2 aerogel composite fiber materials can not only greatly improve the thermal insulation performance of phase change paraffin-SiO2 aerogel composite fiber materials, but also enhance its toughness and reduce its density. At the same time, the porous structure in the SiO2 aerogel composite fiber material can also stabilize the phase change process of highly dispersed phase change paraffin and extend the service life of phase change paraffin. In addition, the phase change paraffin and SiO2 sol are compounded into a composite sol, which not only realizes the precise control of the amount of phase change paraffin added, but also avoids the problem of fiber material carrier damage caused by the inability to control the amount of phase change paraffin added, and maximizes the overall performance of the phase change paraffin-SiO2 aerogel composite fiber material.

[0062] In cationic surfactants, one end of the molecule is a hydrophilic group with a positive charge, and the other end is a hydrophobic group, so it can significantly reduce the tension between the two interfaces, so that the two incompatible substances form a relatively stable dispersion system. When acting on the composite sol system, the hydrophilic group with a positive charge can interact with the negatively charged surface of silica, and the hydrophobic tail interacts with the phase-change paraffin, thereby effectively reducing the surface tension between the liquid and the liquid, and promoting the uniform dispersion of the two; at the same time, the cationic surfactant will form a water-in-oil structure when dispersing the phase-change paraffin and SiO2 sol, which can be used as a structural directing agent to assist the formation of pores in the phase-change paraffin-SiO2 aerogel composite fiber material. The use of cationic surfactants to mix phase-change paraffin and SiO2 sol also further improves the dispersibility of the phase-change paraffin, ensuring that the composite sol can be evenly immersed in the fiber substrate, and realizing the improvement of the performance of the phase-change paraffin-SiO2 aerogel composite fiber material.

[0063] The main component of the glass fiber substrate is glass fiber, which has the characteristics of low density, high heat resistance, low thermal expansion coefficient and good chemical resistance. When used as a fiber substrate for aerogel composite materials, it can improve the mechanical properties of aerogel composite materials. However, the chemical groups on the surface of the glass fiber substrate are usually not active enough. When used as a fiber substrate for phase change paraffin-SiO2 aerogel composite fiber materials, it may cause difficulty in the adhesion of the composite sol; at the same time, the presence of 7-15% of resin colloids used for bonding in the glass fiber substrate may cause pore blockage, which is not conducive to the infiltration of the composite sol. By calcining the glass fiber substrate, the chemical groups on the surface of the glass fiber substrate can be effectively activated to ensure the uniform adhesion of the composite sol. At the same time, high-temperature calcination can also improve the purity of the glass fiber substrate, remove self-contained colloids, and further uniformize the pore structure during calcination, eliminate the internal stress of the glass fiber, and achieve further improvement in the performance of the fiber substrate of the phase change paraffin-SiO2 aerogel composite fiber material.

[0064] As some exemplary preferred schemes, the silicon source in step S1 is selected from any one of orthosilicates and silanes.

[0065] As a further solution, the orthosilicate silicon source is selected from any one of ethyl orthosilicate, methyl orthosilicate, and butyl orthosilicate.

[0066] As a further solution, the silane silicon source is selected from any one of dimethyldiethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane and propyltrimethoxysilane.

[0067] As a further solution, the alcohol in step S1 is selected from a mixture of one or more monohydric alcohols.

[0068] As a further embodiment, the monohydric alcohol is selected from methanol, 95 ethanol, anhydrous ethanol, isopropanol, n-propanol, n-butanol, isobutanol, sec-butanol, and tert-butanol.

[0069] As a further embodiment, the alcohol is selected from a mixture of one or more of methanol, 95 ethanol, isopropanol or anhydrous ethanol.

[0070] As a further solution, the ratio of silicon source:alcohol in step S1 is 1:(10-20).

[0071] As a further solution, the acidic catalyst in step S1 is selected from any one of a strong acid or a medium-strong acid.

[0072] As a further embodiment, the strong acid is selected from any one of perchloric acid, hydroiodic acid, sulfuric acid, hydrobromic acid, hydrochloric acid, nitric acid, and iodic acid.

[0073] As a further embodiment, the medium-strong acid is selected from any one of oxalic acid, sulfurous acid, phosphoric acid, pyruvic acid, and nitrous acid.

[0074] As a further solution, the pH value during the hydrolysis in step S1 is 1.5 to 3.0.

[0075] As a further solution, the hydrolysis temperature in step S1 is 25°C-50°C.

[0076] As a further solution, the hydrolysis time in step S1 is 3-16 hours.

[0077] As a further solution, the phase change paraffin in step S2 is selected from 28-80 series phase change paraffin. 28-80 series phase change paraffin has a more regular and orderly long-chain alkane structure than other series of phase change paraffins, which gives 28-80 series phase change paraffin a higher heat storage capacity and stability, and is also easier to participate in the construction and stabilization of the SiO2 framework with the help of cationic surfactants, thereby achieving the compounding of phase change paraffin.

[0078] As a further solution, the phase change paraffin is selected from 28-40 series phase change paraffin. Compared with 40-80 series phase change paraffin, 28-40 series phase change paraffin has a shorter carbon chain length, which is conducive to better mixing and dispersion with SiO2 sol with the help of surfactants, and building a skeleton with more uniform pores, thereby further improving the heat storage and thermal insulation properties of the phase change paraffin-SiO2 aerogel composite fiber material.

[0079] As a further solution, the phase change paraffin wax in step S2 accounts for 0.5%-3% by mass in the SiO2 sol.

[0080] As a further solution, the alkaline catalyst in step S2 is selected from a mixed solution of an alkaline compound and deionized water.

[0081] As a further embodiment, the alkaline compound is selected from a mixture of one or more of sodium hydroxide, sodium bicarbonate, ammonium fluoride or ammonia water.

[0082] As a further solution, the mass ratio of the alkaline catalyst to the deionized water in step S2 is alkaline compound:deionized water=1:100.

[0083] As a further solution, the mass ratio of the alkaline catalyst to the composite sol in step S2 is 1:100-1:20 (adjusted according to the required gel time).

[0084] As a further solution, the cationic surfactant in step S2 is selected from any one of an amine salt type cationic surfactant, a quaternary ammonium salt type cationic surfactant and a heterocyclic type cationic surfactant.

[0085] As a further solution, the cationic surfactant in step S2 is selected from any one of a quaternary ammonium salt cationic surfactant and a heterocyclic cationic surfactant.

[0086] As a further solution, in step S2, the cationic surfactant is selected from a quaternary ammonium salt cationic surfactant. For non-quaternary ammonium salt cationic surfactants, the positively charged cations are greatly affected by pH, multivalent ions and electrolytes. In contrast, quaternary ammonium salt cationic surfactants are not only unaffected by pH, but can also be dissociated into positively charged surfactant ions, which better assist the construction of the phase change paraffin and SiO2 framework, so as to further improve the performance of the phase change paraffin-SiO2 aerogel composite fiber material.

[0087] As a further solution, the quaternary ammonium salt type cationic surfactant is selected from a quaternary ammonium salt type cationic surfactant having a C10-C20 long-chain alkyl group. The quaternary ammonium salt type cationic surfactant having a C10-C20 long-chain alkyl group can better assist the phase-change paraffin wax having a long-chain alkyl group in building a framework, especially the 28-40 series of phase-change paraffin waxes. Due to the similar alkyl long-chain structure, with the help of the quaternary ammonium salt type cationic surfactant, a phase-change paraffin wax-SiO2 aerogel composite fiber material with a more uniform pore size can be constructed, further improving its thermal insulation performance.

[0088] As a further solution, the quaternary ammonium salt cationic surfactant is selected from any one of cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride, cetylpyridinium chloride, benzyldimethyloctadecylammonium chloride, dodecylpyridinium chloride, and cetyltrimethylpyridinium chloride.

[0089] As a further solution, in step S2, the mass of the surfactant in the SiO2 sol accounts for 0.1%-10%.

[0090] As a further solution, in step S3, the glass fiber substrate is selected from any one of needle-punched glass fiber mat, wet-process glass fiber mat, chopped glass fiber mat, continuous glass fiber mat, knitted glass fiber mat, high-silica glass fiber mat, and silicon carbide glass fiber mat.

[0091] As a further solution, the high temperature treatment method in step S3 is not limited, and technicians can choose according to actual needs, including muffle furnace calcination, tubular furnace calcination, and electric arc furnace calcination.

[0092] As a further solution, the glass fiber substrate treatment temperature in step S3 is 250°C-400°C.

[0093] As a further solution, the glass fiber substrate treatment temperature in step S3 is 280°C-350°C.

[0094] As a further solution, the glass fiber substrate treatment time in step S3 is 3h-6h.

[0095] As a further solution, the glass fiber substrate treatment time in step S3 is 3.5h-4.5h.

[0096] As a further solution, the vacuum degree of the vacuum box in step S3 is -0.15MPa to -0.05MPa.

[0097] As a further solution, the immersion time in step S3 is 5-15 minutes.

[0098] As a further solution, the gel time in step S3 is 50-180 min.

[0099] As a further solution, the aging liquid in step S4 is selected from alcohols, silanes or a mixture of both.

[0100] As a further embodiment, the alcohol is selected from one or a mixture of two monohydric alcohols.

[0101] As a further embodiment, the monohydric alcohol is selected from methanol, ethanol, isopropanol, n-propanol, n-butanol, isobutanol, sec-butanol, and tert-butanol.

[0102] As a further embodiment, the silanes are selected from one or a mixture of organic silanes, inorganic silanes, and fluorinated silanes.

[0103] As a further embodiment, the organosilanes are selected from methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, 3-epoxypropyltrimethoxysilane, 3-epoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, or a mixture of two thereof.

[0104] As a further embodiment, the inorganic silanes are selected from one or a mixture of two of tetraethoxysilane, tetramethoxysilane, tetrapropoxysilane, tetrabutoxysilane, sodium silicate, potassium silicate, lithium silicate, trichlorosilane, dichlorodiethoxysilane, and monochlorotriethoxysilane.

[0105] As a further embodiment, the fluorine-containing silane is selected from one or a mixture of two of trifluoropropyltrichlorosilane, trifluoropropyltriethoxysilane, trifluoropropyltrimethoxysilane, 3-fluoropropyltrimethoxysilane and 3-fluoropropyltriethoxysilane.

[0106] As a further solution, the aging temperature in step S4 is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, or 70°C.

[0107] As a further solution, the supercritical temperature of ethanol in step S5 is 250-270°C.

[0108] As a further solution, the supercritical pressure of ethanol in step S5 is 8-12 MPa.

[0109] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0110] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0111] Example 1

[0112] A method for preparing a phase-change paraffin wax-SiO2 aerogel composite wet-process glass fiber felt material in this embodiment includes:

[0113] Ethanol and ethyl orthosilicate were mixed and stirred evenly in a molar ratio of 19:1, hydrochloric acid was added to adjust the pH to 1.5, and the mixture was hydrolyzed in an oven at 40°C for 8 h.

[0114] Sodium bicarbonate and deionized water were mixed evenly in a mass ratio of 1:100 as an alkaline catalyst. A water bath was heated to 40°C, 28 paraffin was melted into a colorless and transparent solution, and then added to the SiO2 sol and stirred evenly, and alkaline catalyst and CTAB were added at the same time, wherein the mass proportion of 28 paraffin in the SiO2 sol was 0.5%, and the mass proportion of alkaline catalyst and CTAB in the SiO2 sol was 1%;

[0115] The wet glass fiber felt was treated at high temperature in a muffle furnace at 300°C for 4 hours, taken out and quickly placed in the composite sol, immersed in a vacuum box with a vacuum degree of -0.1MPa for 5 minutes, taken out and allowed to stand at room temperature for 100 minutes to allow it to gel, then placed in ethanol aging solution and aged in a 45°C oven for 10 hours.

[0116] The samples were dried using supercritical ethanol, pressurized to 9 MPa, and the drying kettle temperature was set to 250°C.

[0117] The above phase change paraffin type, phase change paraffin dosage, surfactant type / dosage, fiber type, fiber treatment time and temperature, and drying method are shown in Table 1.

[0118] Embodiments 2 to 12

[0119] The preparation parameters of Example 1 were changed, and the phase change paraffin wax-SiO2 aerogel composite fiber material was prepared in the same manner as in Example 1. The parameter changes are listed in Table 1.

[0120] Comparative Examples 1-6, 9

[0121] The preparation parameters of Example 1 were changed, and the phase change paraffin wax-SiO2 aerogel composite fiber material was prepared in the same manner as in Example 1. The parameter changes are listed in Table 1.

[0122] Comparative Examples 7-8

[0123] The preparation parameters of Example 1 were changed, wherein the CO2 supercritical drying conditions for the sample were: pressurized to 13 MPa, and the drying kettle temperature was set to 45°C. The rest of the phase change paraffin-SiO2 aerogel composite fiber material was prepared in the same manner as in Example 1. The parameter changes are listed in Table 1.

[0124] Thermal insulation performance test method (sample size: 120*120mm)

[0125] according to Figure 6 The device tests the thermal insulation performance; first, measure and record the sample thickness, place two 0.3mm thick PI films close to the sample up and down, arrange the thermocouple close to the sample at the marked part of the PI film, and fix it with PI tape. Set the heating table temperature to 500℃, place the glued sample on the heating table, place a 10mm aluminum block on the top of the sample for gravity fixation, start heating, and record the thermocouple temperature rise curve after the heating table temperature stabilizes at 500±15℃; record the 5min hot surface @ cold surface temperature data and evaluate the maximum temperature of the cold surface, as well as the corresponding hot and cold surface temperature difference when the cold surface is at the maximum temperature.

[0126] Table 1

[0127]

[0128]

[0129]

[0130] Table 2 shows the effects of different synthesis conditions on the performance of phase change paraffin wax-SiO2 aerogel composite fiber materials. It can be seen from Examples 1-12 and Comparative Examples 1 and 3 that the addition of phase change material is the key to improving the performance of phase change paraffin wax-SiO2 aerogel composite fiber materials. Compared with Comparative Example 1 ( Figure 3 ), after adding phase change material (Examples 1-12, Comparative Example 3), the phase change material-SiO2 aerogel composite fiber material exhibits higher thermal insulation capacity, indicating that the heat storage effect of the phase change material improves the thermal insulation performance of the composite material. For different types of phase change materials, Examples 1-12 using phase change paraffin as the phase change material overall show higher performance than Comparative Example 3 using calcium chloride hexahydrate as the phase change material. This may be because the phase change paraffin as the phase change material has better compatibility with CTAB, SiO2 sol as a surfactant, and wet-processed glass fiber felt as a fiber substrate, thereby improving the thermal insulation performance of the phase change paraffin-SiO2 aerogel composite fiber material to a greater extent. In addition, since the phase change paraffin also has higher toughness and lower density, after selecting the phase change paraffin as the phase change material (Examples 1-12), the phase change paraffin-SiO2 aerogel composite fiber material is higher than the comparative examples 1 and 3 in which the phase change paraffin is not added and calcium chloride hexahydrate is selected as the phase change material. The overall thermal insulation capacity, lighter density and higher toughness improve the thermal insulation performance of the phase change paraffin-SiO2 aerogel composite fiber material. In addition, Examples 1-5 and Comparative Example 9 show that as the proportion of the phase change paraffin in the SiO2 sol gradually increases, when it reaches 20%, the thermal conductivity at room temperature decreases significantly (0.01526W / m·K). This is because the excessive phase change paraffin affects the structure of the SiO2 gel, thereby reducing the heat transfer at room temperature, causing the thermal conductivity at room temperature to drop rapidly. In addition, the temperature difference between the hot and cold surfaces of Comparative Example 9 at 500°C for 5 minutes is only 172°C. This may be because the addition of excessive phase change paraffin causes the phase change paraffin to destroy the SiO2 three-dimensional framework when it undergoes a phase change, causing the pores to become blocked and collapsed, making it impossible to continue to maintain the dispersion of the phase change paraffin, and resulting in uneven thermal insulation. The overall performance of the phase change paraffin-SiO2 aerogel composite fiber material is reduced. At the same time, in order to ensure the basic performance of the phase change paraffin-SiO2 aerogel composite fiber material, the proportion of phase change paraffin in the SiO2 sol should be maintained between 0.1% and 10%.

[0131] Example 2 and Comparative Example 2 reflect the influence of the type of surfactant on the phase change paraffin-SiO2 aerogel composite fiber material. When a cationic surfactant (Example 2) is used, the thermal insulation performance of the phase change paraffin-SiO2 aerogel composite fiber material at 500°C is 69°C higher than that when an anionic surfactant (Comparative Example 2) is used. This is because the positively charged hydrophilic groups in the cationic surfactant can attract the negatively charged SiO2 through charge interaction, thereby better realizing the dispersion of the phase change paraffin in the SiO2 sol; while sodium dodecylbenzene sulfonate, as an anionic surfactant, not only repels the negatively charged SiO2, but also easily absorbs moisture and agglomerates. It is difficult to play a fusion role when combined with the composite sol. On the contrary, agglomeration increases solid phase conduction, resulting in poor thermal insulation. Therefore, Comparative Example 2 exhibits lower thermal insulation performance.

[0132] From Example 2 and Comparative Example 4, it can be observed that when the wet-process glass fiber felt that has not been calcined is used to prepare the phase change paraffin wax-SiO2 aerogel composite fiber material, the thermal insulation performance is poor, the toughness is low, and the density is not reduced. This may be because the calcination activates the functional groups on the surface of the glass fiber substrate, removes the glue substances and other impurities used for the bonding of the substrate itself, optimizes the internal pore structure, forms more uniform and orderly pores, eliminates the stress between the structures, and thus improves the performance of the fiber substrate of the phase change paraffin wax-SiO2 aerogel composite fiber material. In addition, the choice of fiber substrate will also affect the various properties of the phase change paraffin-SiO2 aerogel composite fiber material. It can be observed from Example 2 and Comparative Examples 5-6 that the phase change paraffin-SiO2 aerogel composite fiber material using a glass fiber substrate has the best thermal insulation performance, the best density, the best toughness and a lower room-temperature thermal conductivity. This is because the functional groups on the surface of the glass fiber substrate can be activated by calcination, while the pre-oxidized silk fiber substrate composed of oxidized PAN (Comparative Example 5) not only cannot provide active groups that are easier to attach to the composite sol, but PAN is carbonized at high temperature, resulting in structural changes, thereby greatly reducing the thermal insulation capacity of the phase change paraffin-SiO2 aerogel composite fiber material. When a ceramic fiber substrate (Comparative Example 6) is used as a supporting material, since it is usually composed of oxides such as aluminum oxide (Al2O3), zirconium oxide (ZrO2), etc., and the substrate requires a higher glue content to bond together during the preparation process, the chemical bonding between the SiO2 aerogel and the phase change paraffin is weak, and it is difficult to ensure the fixation of the composite sol only by means of van der Waals forces, etc. After being treated at 500°C for 5 minutes, the temperature difference between the hot and cold surfaces is only 138°C, which is much lower than Example 2 using glass fiber as the fiber substrate.

[0133] The drying method is also a key factor affecting the performance of the phase-change paraffin-SiO2 aerogel composite fiber material. Example 2 and Comparative Examples 1, 7, and 8 demonstrate the effects of using ethanol supercritical and CO2 supercritical drying on the performance of the phase-change paraffin-SiO2 aerogel composite fiber material. When using ethanol supercritical drying, the phase-change paraffin-SiO2 aerogel composite fiber material exhibits higher thermal insulation performance, better density, toughness, and lower room-temperature thermal conductivity. At the same time, the hydrophobicity of Example 2 using ethanol supercritical drying can reach 98.5%, which is much higher than that of Comparative Example 8 using CO2 supercritical drying. This may be because the ethanol supercritical drying process can cause the phase-change paraffin-SiO2 aerogel composite fiber material to form a structure with a uniform and thick skeleton structure and uniform pores (such as Figure 4 ). In contrast, the comparative example 6 (such as Figure 5 ) presents an irregular pore structure and cannot provide support and protection for the phase change of phase change paraffin. Therefore, the use of ethanol supercritical drying phase change paraffin-SiO2 aerogel composite fiber material can further improve its heat resistance.

[0134] Examples 1-3 and 10-12 show the effects of different series of phase change paraffin waxes on the performance of phase change paraffin wax-SiO2 aerogel composite fiber materials when used as phase change materials. Compared with 52 phase change paraffin wax, the phase change paraffin wax-SiO2 aerogel composite fiber material using 28 phase change paraffin wax exhibits better performance at the same amount of phase change paraffin wax. This may be because 28 phase change paraffin wax has a shorter carbon chain length and can be better composited with SiO2 aerogel composite fiber materials with the help of cationic surfactants, thereby further improving the overall performance of phase change paraffin wax-SiO2 aerogel composite fiber materials. Therefore, according to Examples 1-5 and 10-12, 28-40 series phase change paraffin waxes can be preferably used as phase change materials.

[0135] Examples 1-5 demonstrate the effects of different proportions of phase change paraffin in the composite sol on the performance of the phase change paraffin-SiO2 aerogel composite fiber material. When the proportion of 28 phase change paraffin is 0.1%, the phase change paraffin-SiO2 aerogel composite fiber material exhibits a low thermal insulation ability at 500°C. As the proportion increases from 0.1% to 0.5%, the temperature difference between the hot and cold surfaces can reach 193°C. This is because the increase in the amount of 28 phase change paraffin results in more 28 phase change paraffin molecules in the phase change paraffin-SiO2 aerogel composite fiber material that phase change at high temperatures, thereby improving the thermal insulation performance. As the proportion of 28 phase-change paraffin wax continues to increase, when the proportion of 28 phase-change paraffin wax reaches 3%, the thermal insulation performance is similar to that of 0.5%. This may be due to the excessive 28 phase-change paraffin wax filling the micropores in the phase-change paraffin wax-SiO2 aerogel composite fiber material, causing the porous structure of the aerogel to be destroyed, thereby reducing the pore volume in the material and affecting the thermal insulation performance of the material. In addition, as the proportion of paraffin wax gradually increases, the thermal conductivity of the phase-change paraffin wax-SiO2 aerogel composite fiber material at room temperature shows a slow downward trend. This may be because the introduction of phase-change paraffin wax changes the overlap of part of the SiO2 gel, resulting in a decrease in thermal conductivity at room temperature. Therefore, according to Examples 1-5, it is preferred that the proportion of phase-change paraffin wax in the SiO2 sol is 0.5%-3%.

[0136] In addition, according to Example 2, when a quaternary ammonium salt type cationic surfactant is selected, due to its stability in an acid-base environment, a more stable adsorption layer can be formed at the interface of SiO2 and phase-change paraffin to prevent the aggregation and sedimentation of particles, thereby maintaining the uniform dispersion of the composite sol, so Example 2 shows better heat insulation ability and basic performance. It can also be observed from Example 2 that when a long-chain alkyl group exists in the quaternary ammonium salt type cationic surfactant, the long-chain alkyl group can better assist the phase-change paraffin and SiO2 sol to establish a stable dispersed system. When a C10-C20 long-chain alkyl group is selected, since the length is close to that of the 28-40 series phase-change paraffin alkyl group, it can be used as a template to assist in the construction of a phase-change paraffin-SiO2 aerogel composite fiber material with more uniform pores.

[0137] In addition, the fiber substrate treatment temperature and treatment time will also affect the state of the fiber substrate, thereby affecting the performance of the phase-change paraffin-SiO2 aerogel composite fiber material. It can be observed from Examples 2, 6-7 that as the treatment temperature rises from 250°C to 300°C, the thermal insulation performance of the prepared phase-change paraffin-SiO2 aerogel composite fiber material gradually increases. This may be due to the low temperature of 250°C (Example 6), which cannot completely activate the active groups in the wet-process glass fiber felt, and cannot completely remove the glue carried by the substrate itself during bonding, resulting in the composite sol being unable to achieve the best fixation state; as the temperature further increases, the temperature difference between the hot and cold surfaces at 500°C in Example 7 is 203°C for 5 minutes, which is slightly lower than that in Example 2. This may be because the high temperature of 400°C may cause a slight collapse of the capillary channels in the wet-process glass fiber felt, thereby reducing the amount of phase-change paraffin infiltration and causing a slight decline in thermal insulation performance. According to Examples 2, 6, and 7, when the fiber material is a glass fiber substrate, the preferred fiber substrate treatment temperature is still 280°C-350°C.

[0138] Examples 2, 8, and 9 show the effect of treatment time on the performance of the phase-change paraffin wax-SiO2 aerogel composite fiber material. When treated for 3 hours, the temperature difference between the hot and cold surfaces of the phase-change paraffin wax-SiO2 aerogel composite fiber material at 500°C for 5 minutes was 181°C, and the density was 310 kg / m 3 , 2MPa compression rate is 49%. As the treatment time is gradually extended to 4h, the thermal insulation performance is significantly improved, the density is reduced, and the toughness is enhanced. The treatment time is further extended to 6h, and the performance of the phase change paraffin-SiO2 aerogel composite fiber material declines slightly. This may be because long-term high-temperature treatment causes some pores in the wet-process glass fiber felt to collapse, which in turn leads to a decrease in the performance of the phase change paraffin-SiO2 aerogel composite fiber material. Therefore, according to Examples 2, 8, and 9, when the fiber material is a glass fiber substrate and the fiber substrate treatment temperature is 280℃-350℃, the treatment time is further preferably 3.5h-4.5h.

[0139] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A phase-change paraffin wax-SiO2 aerogel composite fiber material, characterized in that: The specific steps include: S1: Preparation of SiO2 sol: Mix the silicon source and alcohol evenly according to the molar ratio of silicon source: alcohol = 1: (4-20), and add an appropriate amount of acidic catalyst for hydrolysis; S2: Compounding of phase change wax and SiO2 sol: adding melted phase change wax into SiO2 sol and stirring, adding alkaline catalyst and cationic surfactant at the same time, and mixing into a uniform composite sol, wherein the mass of phase change wax in SiO2 sol accounts for 0.1%-10%; S3: Treatment of glass fiber substrate and preparation of gel: The glass fiber substrate after high temperature treatment is placed in the composite sol for vacuum impregnation and gelation; S4: Aging: After the S3 gel becomes hard, put it into the aging solution for aging; S5: Drying: After aging, ethanol supercritical drying is used to obtain a phase change paraffin-SiO2 aerogel composite fiber material.

2. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: In step S1, the silicon source is selected from any one of orthosilicates and silanes, and the alcohol source is selected from a mixture of one or more monohydric alcohols; Further preferably, it is characterized in that the orthosilicate silicon source is selected from any one of ethyl orthosilicate, methyl orthosilicate and butyl orthosilicate; Further preferably, it is characterized in that the silane silicon source is selected from any one of dimethyldiethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, vinyltriethoxysilane and propyltrimethoxysilane. Further preferably, it is characterized in that the monohydric alcohol is selected from one or more mixtures of methanol, 95 ethanol, anhydrous ethanol, isopropanol, n-propanol, n-butanol, isobutanol, sec-butanol, and tert-butanol; Further preferably, it is characterized in that the ratio of the silicon source:alcohol is 1:(10-20).

3. The phase change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The acidic catalyst in step S1 is selected from any one of a strong acid or a medium-strong acid; Further preferably, it is characterized in that the strong acid is selected from any one of perchloric acid, hydroiodic acid, sulfuric acid, hydrobromic acid, hydrochloric acid, nitric acid, and iodic acid; Further preferably, it is characterized in that the medium-strong acid is selected from any one of oxalic acid, sulfurous acid, phosphoric acid, pyruvic acid and nitrous acid.

4. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The pH value during the hydrolysis in step S1 is 1.5-3.0, the temperature during the hydrolysis is 25° C.-50° C., and the hydrolysis time is 3-16 hours.

5. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The phase change paraffin in step S2 is selected from 28-80 series phase change paraffin; Further preferably, it is characterized in that the phase change paraffin is selected from 28-40 series phase change paraffin; Further preferably, it is characterized in that the mass proportion of the phase change paraffin in the SiO2 sol is 0.5%-3%.

6. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The alkaline catalyst in step S2 is selected from a mixed solution of an alkaline compound and deionized water; Further preferably, it is characterized in that the alkaline compound is selected from one or more mixtures of sodium hydroxide, sodium bicarbonate, ammonium fluoride or ammonia water; Further preferably, it is characterized in that the mass ratio of the alkaline catalyst to deionized water in step S2 is alkaline compound: deionized water = 1:100; Further preferably, it is characterized in that the mass ratio of the alkaline catalyst to the composite sol in step S2 is 1:100-1:20 (adjusted according to the required gel time).

7. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The cationic surfactant described in step S2 is selected from any one of an amine salt type cationic surfactant, a quaternary ammonium salt type cationic surfactant and a heterocyclic type cationic surfactant; Further preferably, it is characterized in that the cationic surfactant in step S2 is selected from any one of a quaternary ammonium salt cationic surfactant and a heterocyclic cationic surfactant; Further preferably, it is characterized in that the cationic surfactant in step S2 is selected from quaternary ammonium salt cationic surfactant; Further preferably, it is characterized in that the quaternary ammonium salt type cationic surfactant is selected from quaternary ammonium salt type cationic surfactants having a C10-C20 long-chain alkyl group; Further preferably, it is characterized in that the quaternary ammonium salt type cationic surfactant is selected from any one of cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride, cetylpyridinium chloride, benzyldimethyloctadecylammonium chloride, dodecylpyridinium chloride, and cetyltrimethylpyridinium chloride; Further preferably, it is characterized in that the mass of the surfactant in the SiO2 sol in step S2 accounts for 0.1%-10%.

8. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The glass fiber substrate described in step S3 is selected from any one of needle-punched glass fiber mat, wet-laid glass fiber mat, chopped glass fiber mat, continuous glass fiber mat, knitted glass fiber mat, high-silica glass fiber mat, and silicon carbide glass fiber mat; Further preferably, it is characterized in that the high temperature treatment method in step S3 is not limited, and technicians can choose according to actual needs, including muffle furnace calcination, tubular furnace calcination, and electric arc furnace calcination; Further preferably, it is characterized in that the treatment temperature of the glass fiber substrate in step S3 is 250° C.-400° C.; Further preferably, it is characterized in that the treatment temperature of the glass fiber substrate in step S3 is 280° C.-350° C.; Further preferably, it is characterized in that the glass fiber substrate treatment time in step S3 is 3h-6h; Further preferably, it is characterized in that the glass fiber substrate treatment time in step S3 is 3.5h-4.5h; Further preferably, it is characterized in that the vacuum degree of the vacuum box in step S3 is -0.15MPa to -0.05MPa, and the immersion time is 5-15min.

9. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The aging temperature in step S4 is selected from 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, and the aging liquid is selected from alcohols, silanes, or a mixture of two thereof; Further preferably, it is characterized in that the alcohol is selected from one or a mixture of two monohydric alcohols; Further preferably, it is characterized in that the monohydric alcohol is selected from a mixture of two of methanol, ethanol, isopropanol, n-propanol, n-butanol, isobutanol, sec-butanol and tert-butanol; Further preferably, it is characterized in that the silane is selected from one or a mixture of two of organic silanes, inorganic silanes and fluorinated silanes; Further preferably, it is characterized in that the organosilane is selected from methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, 3-epoxypropyltrimethoxysilane, 3-epoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, or a mixture of two thereof; Further preferably, it is characterized in that the inorganic silane is selected from one or a mixture of two of tetraethoxysilane, tetramethoxysilane, tetrapropoxysilane, tetrabutoxysilane, sodium silicate, potassium silicate, lithium silicate, trichlorosilane, dichlorodiethoxysilane, and monochlorotriethoxysilane; Further preferably, it is characterized in that the fluorine-containing silane is selected from one or a mixture of two of trifluoropropyltrichlorosilane, trifluoropropyltriethoxysilane, trifluoropropyltrimethoxysilane, 3-fluoropropyltrimethoxysilane and 3-fluoropropyltriethoxysilane.

10. The phase-change paraffin wax-SiO2 aerogel composite fiber material according to claim 1, characterized in that: The ethanol supercritical temperature described in step S5 is 250-270° C., and the ethanol supercritical pressure is 8-12 MPa.

Citation Information

Cited By

  • Spacecraft structure with composite phase change thermal control digital intelligent design

    CN119590646A

  • A spacecraft structure designed by composite phase change thermal control and digital intelligence

    CN119590646B